2021
DOI: 10.47665/tb.38.3.088
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal efficacy of temephos impregnated onto kenaf cellulose nanofibre to control Aedes aegypti (Diptera: Culicidae) larvae

Abstract: Larviciding is an effective control method in managing mosquito-borne diseases. However, most of the current larvicide formulations have raised environmental concerns due to the presence of non-biodegradable inert or carrier materials. Therefore, the utilisation of biodegradable natural cellulosic fibres has created much attention. This study aims to evaluate the application of biodegradable kenaf cellulose nanofibre (KCNF) in larvicide formulation where the larvicide, namely temephos, is impregnated onto the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Therefore, it is necessary to develop new, more potent larvicides with better environmental impact. 10 One potential larvicide with better effects on the environment is the use of plant-based larvicides. Several studies have revealed this.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop new, more potent larvicides with better environmental impact. 10 One potential larvicide with better effects on the environment is the use of plant-based larvicides. Several studies have revealed this.…”
Section: Introductionmentioning
confidence: 99%